2004
DOI: 10.1021/bi0498508
|View full text |Cite
|
Sign up to set email alerts
|

Ricin A-Chain Substrate Specificity in RNA, DNA, and Hybrid Stem−Loop Structures

Abstract: Ricin toxin A-chain (RTA) is the catalytic subunit of ricin, a heterodimeric toxin from castor beans. Its ribosomal inactivating activity arises from depurination of a single adenine from position A(4324) in a GAGA tetraloop from 28S ribosomal RNA. Minimal substrate requirements are the GAGA tetraloop and stem of two or more base pairs. Depurination activity also occurs on stem-loop DNA with the same sequence, but with the k(cat) reduced 200-fold. Systematic variation of RNA 5'-G(1)C(2)G(3)C(4)[G(5)A(6)G(7)A(8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…If the opposite was true, false negative signals would be possible with high concentrations of ricin in test samples. The high apparent specificity of ricin toward the dA target residue is consistent with previous findings [17,18]. Indeed, these rate differences may account for the undetectable activity with ricin and RNA GAGA as tested in our study (Fig.…”
Section: '-Rusupporting
confidence: 93%
See 3 more Smart Citations
“…If the opposite was true, false negative signals would be possible with high concentrations of ricin in test samples. The high apparent specificity of ricin toward the dA target residue is consistent with previous findings [17,18]. Indeed, these rate differences may account for the undetectable activity with ricin and RNA GAGA as tested in our study (Fig.…”
Section: '-Rusupporting
confidence: 93%
“…reagents used in the assay were similarly optimized (not shown). Previous research showed that RNA substrates for ricin A chain containing a GdAGA loop exhibited large rate enhancements relative to substrates with a GAGA loop [17,18]. Therefore, we designed a synthetic biotinylated RNA substrate containing a 2 0 -deoxyadenosine (dA) residue within the four-residue loop, GdAGA, in a hairpin structure (RNA GdAGA; Table 1).…”
Section: '-Rumentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the highly specific action on ribosomes, ricin and related RIPs have a less specific action in vitro on super-coiled double-stranded DNA (dsDNA), dsDNA, single-stranded DNA (ssDNA), and RNA substrates releasing multiple adenine residues and, in some instances, guanine residues (Wang and Tumer, 1999). RTA also catalyzes the hydrolysis of synthetic oligonucleotides as short as 6 base pairs, provided a GAGA tetra loop is present (Amukele and Schramm, 2004). Other reported RIP activities are lipase, chitinase, and superoxide dismutase (Xu et al, 2008).…”
Section: N-glycosidase Activity Of Ricinmentioning
confidence: 99%